Antibody producing cells in the spleens of mice treated with pathogenic mineral dust. Issue 10 (October 1989) - Szymaniec, S; Brown, D M; Chladzynska, M; Jankowska, E; Polikowska, H; Donaldson, K
Abstract : Experiments were carried out to assess the effect of intraperitoneal injection of the mineral dusts, titanium dioxide, quartz, or asbestos, on splenic lymphocyte antibody forming cells in immunised mice. Titanium dioxide and quartz caused similar, about one third, reductions in plaque forming cells; asbestos caused substantial reduction to about a quarter of the number found in control spleens. The inhibition of antibody forming cells in the spleen found with chrysotile was dose dependent and both chrysotile and crocidolite asbestos were similar in activity. Systemic immunomodulation after local deposition of mineral dust may be important to the development of disease.